Lithium Protects Against Cartilage Degradation in Osteoarthritis. Issue 5 (May 2014) - Minashima, Takeshi; Zhang, Ying; Lee, Youjin; Kirsch, Thorsten
<x xml:space="preserve">Abstract</x> Objective To determine the actions of lithium chloride (LiCl) on catabolic events in human articular chondrocytes, and the effects of LiCl on the progression and severity of cartilage degradation in interleukin‐1β (IL‐1β)–treated mouse knee joints and after surgical induction of osteoarthritis (OA) in a mouse model. Methods Human articular chondrocytes were treated with LiCl followed by IL‐1β, and the expression levels of catabolic genes were determined by real‐time polymerase chain reaction. To understand the mechanism by which LiCl affects catabolic events in articular chondrocytes after IL‐1β treatment, the activation of NF‐κB was determined using luciferase reporter assays, and the activities of MAPKs and the STAT‐3 signaling pathway were determined by immunoblot analysis of total cell lysates. Cultures of mouse femoral head explants treated with IL‐1β and a mouse model of surgically induced OA were used to determine the effects of LiCl on proteoglycan loss and cartilage degradation. Results LiCl treatment resulted in decreased catabolic marker messenger RNA levels and activation of NF‐κB, p38 MAPK, and STAT‐3 signaling in IL‐1β–treated articular chondrocytes. Furthermore, LiCl directly inhibited IL‐6–stimulated activation of STAT‐3 signaling. Consequently, the loss of proteoglycan and severity of cartilage destruction in LiCl‐treated mouse knee joints 8 weeks after OA induction surgery or in LiCl‐treated mouse femoral head explants after IL‐1β treatment were markedly reduced compared to that in vehicle‐treated joints or explants. Conclusion LiCl reduced catabolic events in IL‐1β–treated human articular chondrocytes and attenuated the severity of cartilage destruction in IL‐1β–treated mouse femoral head explants and in the knee joints of mice with surgically induced OA, acting via inhibition of the activities of the NF‐κB, p38, and STAT‐3 signaling pathways.